Y-chromosomal variation in the Czech Republic - Luca, F; Di Giacomo, F; Benincasa, T; Popa, L O; Banyko, J; Kracmarova, A; Malaspina, P; Novelletto, A; Brdicka, R (American journal of physical anthropology, 2007)
To analyze the contribution of the Czech population to the Y-chromosome diversity landscape of Europe and to reconstruct past demographic events, we typed 257 males from five locations for 21 UEPs. Moreover, 141 carriers of the three most common haplogroups were typed for 10 microsatellites and coalescent analyses applied. Sixteen Hg's characterized by derived alleles were identified, the most common being R1a-SRY(10831) and P-DYS257*(xR1a). The pool of haplogroups within I-M170 represented the third most common clade. Overall, the degree of population structure was low. The ages for Hg I-M170, P-DYS257*(xR1a), and R1a-SRY(10831) ap peared to be comparable and compatible with their presence during or soon after the LGM. A signal of population growth beginning in the first millennium B.C. was detected. Its similarity among the three most common Hg's indicated that growth was characteristic for a gene pool that already contained all of them. The Czech population appears to be influenced, to a very moderate extent, by genetic inputs from outside Europe in the post-Neolithic and historical times. Population growth postdated the archaeologically documented introduction of Neolithic technology and the estimated central value coincides with a period of repeated changes driven by the development of metal technologies and the associated social and trade organization.
Keywords: Analysis of Variance; Population Dynamics; Chromosomes, Human, Y; lidský chromozom Y; lidé; DNA primery; Evolution, Molecular; molekulární evoluce; Genetic Variation; analýza rozptylu; Male; Czech Republic; Haplotypes; Microsatellite Repeats; populační dynamika; Česká republika; DNA Primers; haplotypy; mužské pohlaví; genetická variace; mikrosatelitní repetice; Humans